Penentuan Aktivitas Spesifik Radionuklida Alam Sumber Mata Air Panas di Kabupaten Solok Sumatera Barat - Darmawan, Alfian; Muttaqin, Afdhal; Makmur, Murdahayu (Jurnal Fisika Unand, 2025)
Research has been conducted on determination of specific activity of natural radionuclides of hot water source in Solok Regency, West Sumatera. The study aims to determine the specific activity of radionuclides 238U, 232Th, and 40K and initial water parameters from hot water to effort in radiation safety and protection for environment and surrounding communities. Water samples were taken from three places, namely Bukik Gadang, Batu Bajanjang and Bukik Kili. Then the water samples were analyzed for specific activity using HPGe gamma spectrometer which was chopped 72 hours for radionuclides 238U, 232Th and 40K. The results of measuring acidity (pH), temperature and conductivity of water as initial parameters measured in each sample ranged from 6,1-6,5 for pH; 41-52 °C and 156,4-164,7 μS/m. The results of specific activity measurements on the highest samples were found in the 40K radionuclide ranging from (0.20 ± 0.01) Bq/L to (0.58 ± 0.02) Bq/L and the lowest was in 238U at MDC. Some sample measurement results did not detect all radionuclides because the results obtained were below the MDC. The specific activity of 238U, 232Th and 40K samples were below the threshold of PERKA BAPETEN No. 9 of 2009 which indicates that the research location is safe from radiation impacts.